INCLUSIVE EDUCATION: NECESSITY, PROSPECTIVE TREND - Jahangir, Abdullayev; Shonazar, Botirov (PT. Antis International Publisher, 2024)
This article describes the introduction of inclusive education, what it is, about children with disabilities, as well as the positive and negative aspects of inclusive education.